Radiation of High-Energy Gamma Quanta by Ultrarelativistic Electrons on Nuclei in Strong X-ray Fields - Sergei Roshchupkin; Alexander Dubov; Stanislav Starodub (Universe, 2022)
The possibility of radiation of high-energy gamma quanta with energies of the order of 100 GeV by ultrarelativistic electrons on nuclei in strong X-ray fields with intensities up to ∼10<semantics>27<mspace width="4pt"></mspace>Wcm−2</semantics> was theoretically studied. It is shown that this effect can be realized under special experimental conditions in the process of resonant spontaneous bremsstrahlung radiation of ultrarelativistic electrons on nuclei in an external electromagnetic field. These special experimental conditions determine the characteristic energy of the electrons. This characteristic energy should be significantly less than the energy of the initial electrons. Under these conditions, spontaneous gamma quanta are emitted in a narrow cone with energies close to the energy of the initial electrons. Moreover, the resonant differential cross-sections of such processes can exceed the corresponding differential cross-section without an external field by twenty orders of magnitude. The results obtained can explain the occurrence of high-energy gamma quanta near pulsars and magnetars.